2021
DOI: 10.1002/ppul.24931
|View full text |Cite
|
Sign up to set email alerts
|

Novel imaging techniques for cystic fibrosis lung disease

Abstract: With an increasing number of patients with cystic fibrosis (CF) receiving highly effective CFTR (cystic fibrosis transmembrane regulator protein) modulator therapy, particularly at a young age, there is an increasing need to identify imaging tools that can detect and regionally visualize mild CF lung disease and subtle changes in disease state. In this review, we discuss the latest developments in imaging modalities for both structural and functional imaging of the lung available to CF clinicians and researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 152 publications
0
21
0
2
Order By: Relevance
“…Finally, MRI is increasingly used in CF to evaluate structural as well as functional characteristics of the respiratory system. 29 Graeber et al 32 recently showed that the MRI morphology score and perfusion score significantly improved after 8 to 16 weeks of LUM/IVA therapy in a comparable patient cohort. The MRI score is a visual semiquantitative scoring method using conventional proton MRI combined with contrast-enhanced perfusion MRI.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Finally, MRI is increasingly used in CF to evaluate structural as well as functional characteristics of the respiratory system. 29 Graeber et al 32 recently showed that the MRI morphology score and perfusion score significantly improved after 8 to 16 weeks of LUM/IVA therapy in a comparable patient cohort. The MRI score is a visual semiquantitative scoring method using conventional proton MRI combined with contrast-enhanced perfusion MRI.…”
Section: Discussionmentioning
confidence: 94%
“…26,27 Over the past decade, alternative endpoints for clinical research in CF have been proposed, of which the LCI, CT scores and magnetic resonance imaging (MRI) are regarded to be the most promising. 28,29 LCI, CT scores as well as MRI outcomes have shown to be more sensitive to detect early lung disease, which is an important advantage since the progression of CF lung disease is slowing down and the FEV 1 remains within the normal range at older age. 25,30,31 Two previous observational studies showed that LUM/IVA therapy was associated with a decrease in LCI, while no significant changes were observed in ppFEV 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its good solubility and chemical shift sensitivity to the surrounding environment, HP 129 Xe gas MRI has unique advantages for probing the gas exchange function of the lung globally and regionally. It has been widely used for evaluating lung injuries caused by diseases, such as chronic obstructive pulmonary disease [ 43 ], asthma [ 44 ], cystic fibrosis [ 45 ], idiopathic pulmonary fibrosis [ 46 ], and other lung diseases [ 47 ], including COVID-19 [ 48 ]. Moreover, 129 Xe gas MRI offers unique advantages for longitudinal studies, especially those involving children, owing to the absence of ionizing radiation [ 49 ].…”
Section: Evaluation Of Covid-19-related Pulmonary Damage Using 129 Xe Gas Mrimentioning
confidence: 99%
“…The assessment of lung structural changes via chest radiograph has very low sensitivity and specificity ( 9 ), and although computed tomography scan has been shown to enhance the detection of airway abnormalities in young infants and children with CF ( 10 ), the associated radiation dose required for serial monitoring is considered unacceptable to many. In contrast, magnetic resonance imaging (MRI) can be serially performed without radiation, providing detailed reconstructed images for the detection of subtle airway abnormalities.…”
mentioning
confidence: 99%